Rhabdomyolysis Complicating Unrecognized Hypophosphatemia in an Alcoholic Patient - Deepali Kumar; Finlay A McAlister (Canadian Journal of Gastroenterology)
Rhabdomyolysis occurring as a complication of hypophosphatemia has been infrequently described. A 58-year-old male with a history of daily alcohol consumption presented with two generalized tonic clonic seizures secondary to hypovolemic hyponatremia. He was volume-resuscitated, and antiepileptic medication was administered. After three days of hospitalization, the patient developed severe rhabdomyolysis despite the absence of further seizure activity. Serum phosphate levels were depressed. He was treated with intravenous mannitol, alkaline diuresis, and intravenous and oral phosphate supplementation. He recovered uneventfully. Hypophosphatemia can potentially lead to multisystem organ dysfunction including severe rhabdomyolysis. It is, therefore, important to maintain a low threshold for measuring serum phosphate levels in patients admitted to hospital.